(untitled) - Murray, Anna (Hoboken, 2016)
The Complete Software Project Manager: From Planning to Launch and Beyond addresses an interesting problem experienced by today's project managers: they are often leading software projects, but have no background in technology. To close this gap in experience and help you improve your software project management skills, this essential text covers key topics, including: how to understand software development and why it is so difficult, how to plan a project, choose technology platforms, and develop project specifications, how to staff a project, how to develop a budget, test software development progress, and troubleshoot problems, and what to do when it all goes wrong. Real-life examples, hints, and management tools help you apply these new ideas, and lists of red flags, danger signals, and things to avoid at all costs assist in keeping your project on track.
Keywords: Computer software,Phần mềm máy tính; Development,Phát triển